Pragmatism of Polygamous Family In Muslim Society: Beyond Islamic Law - Sam'ani, Sam'ani; Rokhmadi, Rokhmadi; Amin, Nasihun; Zaini, Ahmad; Sarib, Suprijati (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Pragmatism has become a common motive in polygamous marriages, despite ignoring the principles of Islamic law. Issues ranging from unfair treatment and dishonest attitudes towards wives to the rejection of polygamous pregnant wives have colored the attitudes of pragmatic polygamous life. This article reveals pragmatic motives that become the reasons why a woman is willing to be istri selir-sirri (concubine) in polygamy. This research uses a qualitative approach in which data was collected from observation, interviews, and library studies. The findings of this study suggest that pragmatic motives exist in polygamies, such as the husband's economic stability accompanied by lust satisfaction, the woman's needs for social-economic improvement, and the need for comfort and security. The lack of power among women in relation to men of high social and economic status causes them to agree to be the second wife (selir) despite the sirri marriage status, which is officially unregistered and sometimes unknown even to their own family. As the article sees only the pragmatic sides of polygamy, it still needs further development.